Educational Game Development RPG (Role-Playing Game) Introduction of Department for Prospective Students Using RPG Maker MV - Annaba, Datin (Jurnal Manajemen Informatika Medicom (JMI), 2025)
Several studies state that many students have the wrong major and things this causes problems for them. Data obtained through questionnaires (2016) in 40 respondents of students majoring in informatics engineering, as much as 65% admitted that he was in the wrong major and the biggest cause was misperception. All respondents agree if there is a game that can introduce engineering majors informatics to prospective students of informatics engineering. Then from the questionnaire another with 30 respondents, prospective informatics engineering students can be withdrawn The conclusion is that most of them still do not really know the majors. There are educational games that successfully teach users and game genres Indonesian gamers' favorite is the RPG genre. Therefore the researchers made a game RPG education to introduce informatics engineering majors. Game creation using the method of collecting data from literature and questionnaires, while game development using the Ramadan & Widyani GDLC method. The software used in making this game is RPG Maker MV. After the game is over, it is tested on 30 prospective engineering student respondents informatics, the result is 80% of respondents stated their perception about the majors information technology is changing.